Perception of coaching efficacy : a comparison between athletes of individual and team-based sports - Gan, Sharleen Hui Ling (2017)
This study aimed to identify if athletes' perception of their coach's effectiveness had an effect on the following athlete-related outcomes- enjoyment and commitment in sports, as well as perception of their own physical abilities. It also aimed to establish if there is a difference in how individual and team-based sports athletes perceive coaching effectiveness. Participants were 204 competitive athletes (individual = 100, team = 104) who completed a questionnaire measuring their perception of their coach's effectiveness in four subscales, as well as their enjoyment and commitment in sport, and their perceived physical ability. Correlation tests were carried out to determine if there was a relationship between the athletes' perception of coaching effectiveness and the athlete-related outcomes. A Mann-Whitney U test was run to determine if there was a difference in how individual and team sport athletes score their coaches' effectiveness. There was a significant, positive relationship between athletes' perceptions of coaching effectiveness and the measured athlete-related outcomes but no significant differences in the scores of coaching effectiveness between individual and team sport athletes. Perception of coaching effectiveness had the strongest impact on the enjoyment of athletes out of the measured athlete-related outcomes. In conclusion, perception of athletes regarding the effectiveness of their coaches can implicate the enjoyment; commitment, and perceived physical ability of athletes but the type of sport may not influence an athlete's perception of their coach's effectiveness.